2011
DOI: 10.1007/s11357-011-9300-y
|View full text |Cite
|
Sign up to set email alerts
|

Presbypropria: the effects of physiological ageing on proprioceptive control

Abstract: Several changes in the human sensory systems, like presbycusis or presbyopia, are wellknown to occur with physiological ageing. A similar change is likely to occur in proprioception, too, but there are strong and unexplained discrepancies in the literature. It was proposed that assessment of the attentional cost of proprioceptive control could provide information able to unify these previous studies. To this aim, 15 young adults and 15 older adults performed a position matching task in single and dual-task par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 118 publications
10
41
1
1
Order By: Relevance
“…Taken together, observations from experiment 2 suggest that active older adults may delay their natural decline in proprioception by more effective activation of brain networks associated with sensory processing and cognitive control (Nagamatsu et al 2012;Smith et al 2011;VoelckerRehage et al 2011;see review Voelcker-Rehage and Niemann 2013). This hypothesis is consistent with observations from recent studies showing that age-related declines in proprioception of the lower limb may particularly be visible in challenging conditions that demand more attention (Boisgontier et al 2012;Boisgontier and Nougier 2013;see review Boisgontier et al 2013). Future research may investigate the hypothesis by adding conditions without visual feedback in which aiming movements with high accuracy and/or attentional demands are executed under a strict time constraint.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, observations from experiment 2 suggest that active older adults may delay their natural decline in proprioception by more effective activation of brain networks associated with sensory processing and cognitive control (Nagamatsu et al 2012;Smith et al 2011;VoelckerRehage et al 2011;see review Voelcker-Rehage and Niemann 2013). This hypothesis is consistent with observations from recent studies showing that age-related declines in proprioception of the lower limb may particularly be visible in challenging conditions that demand more attention (Boisgontier et al 2012;Boisgontier and Nougier 2013;see review Boisgontier et al 2013). Future research may investigate the hypothesis by adding conditions without visual feedback in which aiming movements with high accuracy and/or attentional demands are executed under a strict time constraint.…”
Section: Discussionsupporting
confidence: 91%
“…The splitting of the total error into variable and constant errors showed that this decrease in the overall end-point performance was mainly related to the constant error, evidencing an overshooting behaviour in the older adults as compared to the young ones. This result supported the study of Boisgontier et al (2012) which showed that older adults overshot the proprioceptive target when the cognitive load increased. Together, these results suggested that when they have to deal with a stressor (temporal or cognitive) in a proprioceptive task, older adults overshoot rather than undershoot the target.…”
Section: End-point Performancessupporting
confidence: 89%
“…This absence of significant age-related difference supported previous studies showing that older adults were able to reach levels of proprioceptive control performance comparable to those observed in young adults (Batavia et al 1999;Boisgontier et al 2012;Deshpande et al 2003;Goble et al 2012a, b;Marks 1996;Pickard et al 2003). The splitting of the total error into variable and constant errors confirmed this similar pattern of end-point results between age groups.…”
Section: End-point Performancessupporting
confidence: 88%
See 2 more Smart Citations